Repeated intratracheal instillation effects of commonly used vehicles in toxicity studies with mice - In-Hyeon Kim; Je-Hein Kim; Se-Woong Park; Su-Jin Lim; Jeong Hwan Kim; Cheoljin Park; Jinsoo Lee; Sung-Hwan Kim (Scientific Reports)
Abstract Intratracheal instillation (ITI) is considered the most pragmatic approach for investigating the potential toxicities of various respiratory exposure materials. Various respiratory exposure materials, including nanomaterials, hazardous air pollutants, fine dust, and household biocides, have raised public health concerns because of limited toxicological information and increasing consumption. Hence, toxicity studies using ITI in laboratory animals are important to accurately assess the human risks associated with these respiratory-exposed materials. However, data to adequately support the study design of ITI toxicity studies, particularly those examining the effects of commonly used vehicles following repeated exposure are insufficient. Therefore, in this study, we examined the effects of 16 types of commonly used vehicles in toxicity studies following 14-day repeated ITI in mice. General health endpoints (mortality, clinical signs, and body weight) were monitored throughout the study period, and terminal endpoints (gross observation, lung weight, bronchoalveolar lavage fluid analysis, and lung histopathological examination) were assessed after terminal sacrifice. Saline and phosphate-buffered saline elicited the least response, whereas corn oil (50 µL) showed the most severe toxicity findings. In addition, several commonly used vehicles, including distilled water, sodium carboxymethyl cellulose, dimethyl sulfoxide, ethanol, Tween 20, and Tween 80, induced mild-to-severe toxicity in the respiratory system. Based on the results of this study, some commonly used vehicles in toxicity studies should be used with caution when the ITI exposure route is considered. These results provide important background information on the effects of vehicles in ITI toxicity studies along with valuable insights for designing toxicity studies using respiratory exposure materials.